Determinants of Financial Distress of Commercial Banks of Nepal - Maheshwari, Poonam Memani (New Journey, 2024)
According to bankers, economists, and regulators, bank runs, and failures are costly to the economy. Thus, banking stability is of utmost importance. Identifying banks more prone to financial distress is urgent before the effects of their financial instability are felt in the economy. Nonetheless, a great deal of research has been done on the topic, and the findings of these studies are highly inconsistent. Based on this scenario, this paper used the existing model of Altman’s Z-score and another important variable from previous studies. It also provides a systematic framework for predicting the financial distress of Nepalese Commercial Bank. The study selected 12 commercial banks and collected data from 2018/19 to 2022/23. The study found that, on average, the Z-score of Nepalese commercial banks is 32.14, more significant than the cutoff point Z> 2.99. This indicates that the financial institution is in a good position and safe from financial problems. Besides, the study chose four accounting variables suggested by Altman (1968) and found that the liquidity ratio, reserve ratio, return on asset ratio, and book-to-market ratio have positive and significant impacts on the Z-score; Leverage has a positive but insignificant impact on the Z-score. However, size has a negative and insignificant impact on the Z-score. Besides, this study conducted a multicollinearity test, which shows all the values of individual variables are less than 10, indicating no multicollinearity problem in the independent variable.